Analysis of Lavandula angustifolia Aromatherapy Relaxation on Stress Levels and Sleep Quality in Kidney Failure Patients - Orchida, Tidy; Prasetyo , Joko; Dewi, Prima (Poltekkes Kemenkes Tanjung Karang, 2025)
Kidney failure is a condition in which the kidneys are unable to perform essential functions, including filtering waste products, regulating fluid and electrolyte balance, and producing hormones. This study aimed to analyze the effects of relaxation combined with Lavandula angustifolia aromatherapy on stress levels and sleep quality in patients with kidney failure. A quantitative experimental design with a pre-test and post-test control group was employed, involving 30 respondents selected through simple random sampling. Stress levels were measured using the DASS-21, and sleep quality using the PSQI. Data were analyzed using the Mann-Whitney U test and the independent t-test, depending on the distribution of the data. Before the intervention, the mean stress score was 18.47±4.21 in the control group and 17.93±4.10 in the intervention group. After the intervention, the intervention group showed a significant stress reduction (mean 11.20±3.45) compared to the control group (17.40±3.98), as assessed by a Mann-Whitney U test (p=0.0046). Sleep quality also improved significantly, with pre-intervention PSQI scores of 12.33±2.14 (control) and 11.87±2.08 (intervention), and post-intervention scores of 8.20±1.96 (intervention) versus 12.07±2.11 (control), supported by a p=0.0004. The findings demonstrate that Lavandula angustifolia aromatherapy relaxation effectively reduces stress and improves sleep quality in patients with kidney failure. Lavender aromatherapy may serve as a safe, simple, and complementary non-pharmacological therapy to support clinical management in this population.